Establishing the relationships between C9 hydrocarbon resin properties and radical oligomerization technique - Subtelnyy, Roman; Fedotova, Olha; Romaniv, Volodymyr; Zhuravskyi, Yevhenii; Dzinyak, Bohdan (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates the radical oligomerization of the C9 fraction of liquid by-products from diesel fuel pyrolysis. The task addressed is to establish patterns of influence of the radical oligomerization technique on the properties of C9 hydrocarbon resins. The effect of radical oligomerization technique on the physicochemical, molecular weight, rheological, and structural characteristics of resins obtained by high-temperature (thermal, initiated) and low-temperature (emulsion, suspension) methods has been studied. It was established that high-temperature methods provide higher yields of resins (15–32%), lower average molecular weight (455–670 g/mol), and a wider molecular weight distribution (1.20–1.25). Low-temperature dispersion processes are characterized by lower yields (4–29.3%), higher molecular weight (550–750 g/mol) and narrower distribution (1.02–1.06). Emulsion and suspension methods provide lighter resins (10–40 mg I2/100 ml) compared to high-temperature analogs (40–80 mg I2/100 ml). The results and structural differences recorded by IR spectroscopy are attributed to the temperature regime of synthesis. High-temperature resins are characterized by a higher content of condensed cyclic structures. This is explained by the intensification of side chain transfer reactions at high temperatures. Special features of the results are determining the complex relationship between the oligomerization technique and the characteristics of the resins. This allows for a purposeful selection of synthesis conditions for specific product requirements. The scope of practical implementation of the results includes the chemical and paint industries; as well as the possibility of directed regulation of the properties of C9 resins for their use in adhesives, sealants, and film formers